Estimation of Accident Severity and Automatic Notification to Emergency Service - Fenil, E; Dhivya Bharathi, R; Joana Sherly, B (International Journal of Computer Sciences and Engineering, 2014)
In modern day communication technology has been developed a lot. With the help of communications technology in modern vehicles we estimate the people injured in an accident. By using artificial Intelligent system communication takes place between the vehicle to the emergency service and is also notified to the relatives of that person who met the accident .This paper proposes a method which is able to automatically detect road accident, notify them through vehicular network and estimate their severity based on the concept of data mining and knowledge inference. In this project we estimate the severity based upon the vehicle speed, the type of vehicle, status of airbags in the vehicle. It will estimate the severity of accident occurred using Knowledge Discovery Database (KDD) process. We develop a prototype of the vehicle based upon the crash test and previous reports. It totally reduces the time to alert the emergency service.